2011
DOI: 10.1093/annonc/mdq651
|View full text |Cite
|
Sign up to set email alerts
|

Final results of the European Advanced Renal Cell Carcinoma Sorafenib (EU-ARCCS) expanded-access study: a large open-label study in diverse community settings

Abstract: The sorafenib safety profile in European community-based practice settings was similar to that reported in clinical trials. The heterogeneous advanced RCC patient population in EU-ARCCS permitted assessment of sorafenib in important subpopulations of advanced RCC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
104
4
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(122 citation statements)
references
References 13 publications
11
104
4
3
Order By: Relevance
“…As sorafenib is widely used in the treatment of RCC, hepatocellular carcinoma and thyroid carcinoma (17)(18)(19)(20)(21)(22), the oncology community should be alerted to this uncommon but life-threatening adverse event.…”
Section: Discussionmentioning
confidence: 99%
“…As sorafenib is widely used in the treatment of RCC, hepatocellular carcinoma and thyroid carcinoma (17)(18)(19)(20)(21)(22), the oncology community should be alerted to this uncommon but life-threatening adverse event.…”
Section: Discussionmentioning
confidence: 99%
“…(Escudier et al, 2007b) This was consistent with an earlier phase II second line trial that found PFS benefit was independent of age over or under 70 years, prognostic risk, prior cytokine therapy, lung, liver, bone or brain metastases, time from diagnosis, or whether or not the patient had clinical cardiovascular disease. (Beck et al, 2011;Escudier et al, 2007b) The latter included patients with ischemic heart disease, a previous myocardial infarction, left ventricular dysfunction, hypertension, epistaxis or central nervous system ischemia. (Beck et al, 2011) Patients on the placebo arm were permitted to cross over to sorafenib on diagnosis of progressive disease.…”
Section: Sorafenibmentioning
confidence: 99%
“…(Beck et al, 2011;Escudier et al, 2007b) The latter included patients with ischemic heart disease, a previous myocardial infarction, left ventricular dysfunction, hypertension, epistaxis or central nervous system ischemia. (Beck et al, 2011) Patients on the placebo arm were permitted to cross over to sorafenib on diagnosis of progressive disease. In the first interim analysis, a trend towards better OS was noted in patients taking sorafenib, and this was unchanged in the final analysis (17.8 vs. 15.2 months, respectively, HR= 0.88; p = 0.146).…”
Section: Sorafenibmentioning
confidence: 99%
“…Clinical evidence supports the efficacy of sequential treatment with SU/SO [19]; however, the optimal sequence for SO and SU is still under debate, and additional evidence on the optimal use of sequential targeted therapies is advocated.…”
Section: Introductionmentioning
confidence: 99%